2022
DOI: 10.1177/02666669211047916
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cloud Computing Adoption Among SMEs: The Jordanian Context

Abstract: Cloud computing technology has proved to be an important technological solution, especially for small and medium- sized businesses (SMEs), by providing many opportunities for companies to enhance their operations, reduce cost, improve scalability and flexibility, and make more efficient use of technology. Despite its benefits, most SMEs are still hesitant about adopting cloud computing. The purpose of this study is to assess the factors that influence cloud computing adoption among SMEs in Jordan. This study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…TAM has been applied in a variety of contexts, including the adoption of information systems in organizations (Zabadi, 2016), the adoption of mobile technologies (Muflih, 2022), and the adoption of e-learning systems (Al-Adwan, 2020; Al-Adwan, Yaseen, et al, 2022). Researchers have found that TAM is a reliable and valid model for predicting an individual's intention to use technology and that it is able to explain a significant amount of variance in the adoption of technology (Venkatesh et al, 2003).…”
Section: Theoretical Foundation and Development Of Hypotheses Integra...mentioning
confidence: 99%
See 1 more Smart Citation
“…TAM has been applied in a variety of contexts, including the adoption of information systems in organizations (Zabadi, 2016), the adoption of mobile technologies (Muflih, 2022), and the adoption of e-learning systems (Al-Adwan, 2020; Al-Adwan, Yaseen, et al, 2022). Researchers have found that TAM is a reliable and valid model for predicting an individual's intention to use technology and that it is able to explain a significant amount of variance in the adoption of technology (Venkatesh et al, 2003).…”
Section: Theoretical Foundation and Development Of Hypotheses Integra...mentioning
confidence: 99%
“…The TOE model considers the elements of technology, organization, and environment, and the many sub-factors that impact the adoption of innovation (El-Haddadeh, 2020). The TOE model has been used for examining a variety of digital technologies, for example, e-business and e-commerce, and organizational readiness to adopt technological innovation (Awa et al, 2016;Yaseen et al, 2022). Additionally, the TOE model is utilized for testing the implementation of technology by SMEs (Sabi et al, 2018).…”
Section: Theoretical Foundation and Development Of Hypotheses Integra...mentioning
confidence: 99%
“…The ability to recover from node failure is a key benefit of mesh topology-based path protection over links.It can discover a variety of additional routes between every node in the network. Additionally, our suggested method ensures that the traffic between the source and destination will not be lost and that the new way will not be impacted [26], [27].…”
Section: The New Technique and Algorithmmentioning
confidence: 99%
“…Cloud computing technologies have transformed how businesses and individuals interact with data and applications, providing a seamless flow and modern touch to accessing, storing, and managing information (Yaseen et al, 2023). Unlike conventional computing setups dependent on local hardware and software, cloud computing utilizes the internet to deliver computing resources instantly as needed.…”
Section: Introductionmentioning
confidence: 99%